(untitled) (Journal of Organizational Psychology, 2021)
Walker and Watkins (2020) conducted a thematic analysis of the lived experiences of 130 oppressed followers of toxic leaders. The current paper presents a new model of toxic leadership that emerged from the study. Toxic leadership is a phenomenon sanctioned by the organization, perpetuated by the toxic leader, and lived by the oppressed follower. The model situates toxic leadership within an open organizational frame with recommendations for organizational leaders to drive toxic leadership out of their organizations, for leaders to recognize their toxic behaviors, and for followers to cope with toxic leaders.